Gendered violence in Art: a study of Baroque and Classical Ages - Dharmani, Rishya (International Journal of Culture and Art Studies, 2022)
Art and history are always mirrors of each other. Their specific modes of functioning, despite being dissimilar to each other, are still consonant. Consciousness of time is common to them, traveling continuously through the past and future, creating the present. But art; its representation, subversion, methods, spaces, humans and life is sometimes contrarian to the march of history. Art often defies history by rejecting the ’present’ and creating its own utopia. "Indeed, music protects its social truth by virtue of its antithesis to the society, by virtue of isolation, yet by the same measure, this isolation lets music wither. It is as if its stimulus to production, its raison d’être, had been withdrawn.